Oscillatory and alternate flows in a microfluidic device - Oliveira, Hugo Carneiro (2006)
The mixing properties of systems with oscillatory or alternate flows are studied by numerical methods. Preliminary results show that, for alternate flows, the contact area between high and low concentration regions increases and mixing is achieved from the combination of transversal diffusion and axial advection. The improvement in the mixing process shows that this method is very useful for designing mixers in lab-on-a-chip devices.